IMPLEMENTATION OF SPEECH ACTIVITIES TO IMPROVE SPEECH SKILLS AT THE DARUL HIKMAH ISLAMIC BOARDING SCHOOL IN TULUNGAGUNG - Naili Zulfa Wafira; Nurhadi; Fikri, Shofil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of language activities in improving the language skills of students at the Darul Hikmah Islamic Boarding School in Tulungagung, as well as to identify the supporting and inhibiting factors. This study employs a qualitative approach using a case study design. The research subjects include instructors, language coordinators, and students selected through purposive sampling. Data collection techniques were conducted through participant observation, in-depth interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, and its validity was tested through source triangulation. The results of the study indicate that the implementation of kalam activities is conducted in a structured and continuous manner through various language programs, such as morning conversation sessions, vocabulary drills, the application of language immersion, and competitive activities like the weekly language improvement competition. The implementation of these activities is supported by the active role of language coordinators in providing guidance, motivation, and supervision, which aligns with the “actuating” function in management theory. Supporting factors include a conducive language environment, coordinator involvement, diverse programs, and opportunities to participate in language competitions. Meanwhile, inhibiting factors include differences in students’ initial proficiency, low self-confidence, limited vocabulary, and non-compliance with language rules. Overall, the implementation of speech activities has proven to effectively contribute to improving students’ speaking skills.